2008
DOI: 10.1677/joe-08-0057
|View full text |Cite
|
Sign up to set email alerts
|

Early overnutrition impairs insulin signaling in the heart of adult Swiss mice

Abstract: Human overnutrition has caused a rise in the prevalence of obesity in recent years. In addition to the deleterious effects of obesity during childhood, long-term effects in adulthood have been described as well. For instance, cardiovascular diseases and type 2 diabetes are among the diseases associated with a history of obesity. Altered insulin secretion and action have been described as important links between these diseases and obesity. Insulin acts as a unique anabolic hormone providing regulation of wholeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Previously, Rodrigues et al [14] have demonstrated, in the 90-day-old SL rats, lower IRS1, PI-3K and GLUT-4 expressions and lower Akt activity in adipocytes. Also, Martins et al [37] have found that 150 days-old SL Swiss mice had decreased insulin sensitivity in the heart. However, in 1-year-old SL rats, no changes in liver and heart insulin pathway signaling were observed [38].…”
mentioning
confidence: 97%
“…Previously, Rodrigues et al [14] have demonstrated, in the 90-day-old SL rats, lower IRS1, PI-3K and GLUT-4 expressions and lower Akt activity in adipocytes. Also, Martins et al [37] have found that 150 days-old SL Swiss mice had decreased insulin sensitivity in the heart. However, in 1-year-old SL rats, no changes in liver and heart insulin pathway signaling were observed [38].…”
mentioning
confidence: 97%
“…The early postnatal exposure induces elevated body weight and adiposity that persists to adulthood (1012), with concomitant increases in plasma insulin (11,13) and leptin concentrations (13) and impaired glucose tolerance (11,13,14). It remains unresolved, however, whether the sustained increase in adiposity of adult SL rodents results from increased energy intake or decreased energy expenditure (13,15). Moreover, the fundamental mechanisms by which the metabolic effects of SL exposure persist to adulthood are unknown.…”
mentioning
confidence: 99%
“…These exposures change the programming of cardiac metabolism, inducing excessive lipid accumulation in myocardial cells 54,34 and defects in cardiac insulin signaling. 53 In the early origin of cardiac dysfunctions, the existence of sensitive developmental windows of exposure had been only addressed in a few studies which highlighted the impact levels according to the time of exposure. In the case of high-fat diet, adult cardiac alterations including increased heart rate were described when the exposure occurred after weaning.…”
Section: Early Exposure To Environmental Challenges Induces Cardiac Dmentioning
confidence: 99%